Organic carbon concentrations in the woodland and soils of the protected natural area “El Faro” in Tlalmanalco, Estado de Mexico - Cano-Flores, Oscar; Vela-Correa, Gilberto; Acevedo-Sandoval, Otilio A.; Valera-Pérez, Miguel Ángel (REVISTA TERRA LATINOAMERICANA, 2020)
Despite restoration efforts, Mexico loses on average 500 000 ha of temperate forests annually, releasing the carbon stored in plant tissues, leaf litter, and soils into the atmosphere. Much of the temperate forests of Mexico grow on volcanic soils (Andosols), which cover approximately 1.2% of the country’s area. However, little information is available on how much carbon is stored in soil, leaf litter, and arboreal components of these systems. Therefore, the objective of this study was to determine organic carbon concentration in trees, litter, and soil in “El Faro” Protected Natural Area in Tlalmanalco, Mexico State. This research selected eight study sites under four tree-cover categories: Cupressus-Pinus, Pinus-Quercus, Quercus-Pinus and Quercus, and determined species and normal diameter (DN) of trees with DN larger than 10 cm, samples of leaf litter and soil were collected at a depth of 0-20 cm. Soil organic carbon (SOC) concentration was determined in the laboratory in an elemental analyzer, as well as bulk density, porosity, and rock volume. Total carbon stored by trees was estimated using species-specific allometric formulas. The average total carbon content was 185.34 Mg ha-1, with an overall average of 56.40 Mg ha-1 in trees, 44.91 Mg ha-1 in leaf litter, and 84.03 Mg ha-1 in soil. The tree cover storing the most carbon in vegetation was Pinus-Quercus, with 71.74 Mg ha-1, and across all the study sites a positive correlation was recorded between total Quercus tree biomass and SOC. This result was probably due to faster accumulation and decomposition of Quercus leaf litter compared to pine needles. Based on the estimates of this study, 50 ha of El Faro protected natural area stored a total of 9267 Mg of carbon that could be released if the area were deforested, evidencing the importance of its conservation.